PATHOGENESIS OF KIDNEY INJURY IN PATIENTS WITH COVID-19 - Khursandov, I.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The SARS-CoV-2 pandemic has shaken the world since its initial outbreak in December 2019. As of November 2021, the World Health Organization has reported more than 26.1 million cases and 5200000 deaths, and these numbers continue to rise as more and more episodes related to the effects of the disease emerge. Country-by-country mortality rates provided by Johns Hopkins University range from 0.1% to 9.2% with significant geographical differences. Along with damage to the respiratory system and the cardiovascular system, an important role is played by pathologies of the kidneys, which are characterized by the development of both acute and chronic renal failure. Particular difficulties arose in the treatment of patients in need not only of artificial ventilation, but also of hemodialysis, in the need for hospitalization of patients in intensive care units. This was the reason for the development of economic problems in the health care system. This review article is devoted to the pathogenesis of kidney damage in patients with COVID-19.